2012
DOI: 10.1042/bj20111704
|View full text |Cite
|
Sign up to set email alerts
|

A conserved cysteine residue is involved in disulfide bond formation between plant plasma membrane aquaporin monomers

Abstract: AQPs (aquaporins) are conserved in all kingdoms of life and facilitate the rapid diffusion of water and/or other small solutes across cell membranes. Among the different plant AQPs, PIPs (plasma membrane intrinsic proteins), which fall into two phylogenetic groups, PIP1 and PIP2, play key roles in plant water transport processes. PIPs form tetramers in which each monomer acts as a functional channel. The intermolecular interactions that stabilize PIP oligomer complexes and are responsible for the resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 50 publications
6
65
0
Order By: Relevance
“…In mammalian aquaporins, a cysteine located exactly three-residues before the 2nd NPA motif in loop E was revealed to be the mercury-sensitive residue (Jung et al 1994). In plant PIPs, on one hand, a cysteine in loop A was involved in the disulfide bond formation between monomers and, in particular, the mercury-sensitivity in the case of maize PIP (Bienert et al 2012). On the other hand, mercury did not inhibit but increased water permeability via a non-cysteine mechanism in spinach SoPIP2;1 (Frick et al 2013).…”
Section: Arsenite Transportmentioning
confidence: 99%
“…In mammalian aquaporins, a cysteine located exactly three-residues before the 2nd NPA motif in loop E was revealed to be the mercury-sensitive residue (Jung et al 1994). In plant PIPs, on one hand, a cysteine in loop A was involved in the disulfide bond formation between monomers and, in particular, the mercury-sensitivity in the case of maize PIP (Bienert et al 2012). On the other hand, mercury did not inhibit but increased water permeability via a non-cysteine mechanism in spinach SoPIP2;1 (Frick et al 2013).…”
Section: Arsenite Transportmentioning
confidence: 99%
“…No signal was observed in eluted fractions from mock oocytes or oocytes expressing Venus:ZmSYP121 alone ( Figure 5A, lanes c and d). The 6His:ZmPIP2;5 dimeric form was due to the presence of a disulfide bond linking two Zm-PIP2;5 monomers (Bienert et al, 2012) and was detected as no reducing agent was added in the solubilization buffer. Interestingly, a YFP signal corresponding to Venus:ZmSYP121 was observed in the fraction coming from oocytes coexpressing 6His:ZmPIP2;5 and Venus:ZmSYP121 ( Figure 5B, lane b), demonstrating that both proteins were copurified.…”
Section: Zm-pip2;5 and Zm-syp121 Physically Interact In Xenopus Oocytmentioning
confidence: 99%
“…2C; Bienert et al, 2012). This model showed that the TM3 was located on the outer surface of the ZmPIP2;5 tetramer.…”
Section: Tm3 Plays a Role In The Delivery Of Zmpip2s To The Pmmentioning
confidence: 99%
“…Maize mesophyll protoplasts were transiently transformed with genetic constructs encoding the chimeric ZmPIPs fused downstream of the monomeric yellow fluorescent protein (mYFP; see the "Materials and Methods"). Previous studies demonstrated that tagging ZmPIPs with GFP variants at their N terminus does not affect their activity (Fetter et al, 2004;Besserer et al, 2012;Bienert et al, 2012), nor does it prevent N-terminal trafficking motifs to be functional (Zelazny et al, 2009). In plant cells, PM, ER, and cytosol are sometimes difficult to distinguish because of the presence of the central vacuole that occupies most of the cell volume and pushes all other cell compartments against the PM.…”
Section: Tm3 Plays a Role In The Delivery Of Zmpip2s To The Pmmentioning
confidence: 99%